Characterization of lethal alleles of D-elg, an ets proto-oncogene related gene with multiple functions in Drosophila development. - Schulz, R.A.; Hogue, D.A.; The, S.M. (Oncogene, 1993)
We have used genetic complementation rescue to identify two lethal alleles of D-elg, an ets proto-oncogene related gene of Drosophila. Animals that are hemizygous or trans-heterozygous for the alleles die as pharate adults, demonstrating normal gene function is required to complete Drosophila development. Females trans-heterozygous for the 1(3)902 lethal allele and the previously characterized tne female sterile allele produce embryos with abdominal segmentation defects. This finding implicates a role for the D-elg gene in anterior-posterior patterning. The cloning and sequencing of the lethal alleles identified molecular mutations that may result in ELG protein truncation, altered ELG protein interactions, or defective D-elg mRNA splicing.